GENERALIZAREA ACCEPŢIUNILOR ŞTIINŢIFICE MODERNE ASUPRA TIPOLOGIEI ŞI STRUCTURII COMPETENŢEI PROFESIONAL-DIDACTICE - USM ADMIN (Moldova State University, 2011)
This article identifies an opened problem in educational sciences-the typology and the structure of the professional competence of the teachers. There are listed the correlations of this new problem with competence-based professionalization.